Zhores Khachatryan - Karapetyan, Inesa; Margaryan, Hasmik (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
Zhores Khachatryan, the former head of the Department of ‘Archaeology of Ancient Armenia’ of the Institute of Archaeology and Ethnography, NAS RA was one of the most devoted and honored archaeologists in Armenia. He was born in 1935, into a family with their origins in Sivas/Sebastia, which had fled during the Armenian Genocide. After a long and arduous journey, they found a home in Yerevan. After graduating from school, he was accepted to the Faculty of History of the Yerevan State University. He started his academic activities in 1959 as an assistant in the Department of ‘Ancient and Medieval Archaeology’ of the Institute of Archaeology and Ethnography. During 1962-1965 he was a postgraduate student in the Department of ‘Antique Archaeology’ of the same institute. His advisor was Prof. B.N. Arakelyan, one of the leading archaeologists in Armenia. This was an essential school for Zh. Khachatryan for his specialisation in the problems of the Antique Period archaeology and history of Armenia. He worked at that same Institute until the final years of his life (2015).